Konstruksi Sosial Pengurangan Risiko Bencana Berbasis Masyarakat di Kawasan Ekonomi Khusus Mandalika - Efendi, Iwan; Taqiuddin, Muh.; Evendi, Azhari (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2022)
The research is entitled " Social Construction of Community-Based Disaster Risk Reduction in the Mandalika Special Economic Zone ". Sengkol Village is one of the disaster-prone villages, especially in the hamlets of Gerupuk 1, Gerupuk 2, Ebangah which is located in the coastal area. The Village Disaster Preparedness Team (TSBD) was formed as a communitybased disaster risk reduction. This study uses the social construction theory of Peter L. Berger and Luckmann. This research uses a qualitative case study method. Research informants from the management of the Village Disaster Preparedness Team, the CONSEPSI field staff of the Caritas Germany program, and the village head of Sengkol, Central Lombok. Data collection techniques used structured interview techniques, field observations, and documentation results. The data analysis technique used is an interactive model from Milles and Habberman in three (3) ways, namely data reduction, data presentation,and conclusion drawing. The validity technique uses extended observations and triangulation methods to check the level of confidence. The results showed that based on the results of the analysis using social construction theory, Berger and Luckman Social construction are formed through 3 (three) dialectical processes, namely, first, externalization is reflected in the existence of local wisdom in the tsunami early warning system with the appearance of Layur fish on the beach, indicating that a disaster will occur. Second, the objectification process, through the rules for implementing disaster management and philosophical values so that it successfully legitimizes the existence of community-based disaster risk reduction. Third, the internalization process through primary socialization using the TSBD institution to mobilize the community in community-based disaster risk reduction. This becomes the capital in reducing disaster risk in Sengkol Village.